2008
DOI: 10.1098/rspa.2008.0380
|View full text |Cite
|
Sign up to set email alerts
|

On feasible regions of lamination parameters for lay-up optimization of laminated composites

Abstract: The stiffness tensors of a laminated composite may be expressed as a linear function of material invariants and lamination parameters. Owing to the nature of orienting unidirectional laminae ply by ply, lamination parameters, which are trigonometric functions of the ply orientation, are interrelated. In optimization studies, lamination parameters are often treated as independent design variables constrained by inequality relationships to feasible regions that depend on their values. The relationships between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 17 publications
1
79
0
Order By: Relevance
“…Indeed, there are three distinct stability characteristics depending on the value of this ratio. The reader is referred to the work by Bloomfield et al (2009) The strain energy for this particular lay-up is shown in figure 8a, where the edge of the surface describes a flat circle denoting the constant level of strain energy for any helix angle −180 • < 2q < 180 • . This is also observed for a = 2 in the contour plot shown in figure 8b and is highlighted by the dashed circle.…”
Section: Strain Energy Tailoringmentioning
confidence: 99%
“…Indeed, there are three distinct stability characteristics depending on the value of this ratio. The reader is referred to the work by Bloomfield et al (2009) The strain energy for this particular lay-up is shown in figure 8a, where the edge of the surface describes a flat circle denoting the constant level of strain energy for any helix angle −180 • < 2q < 180 • . This is also observed for a = 2 in the contour plot shown in figure 8b and is highlighted by the dashed circle.…”
Section: Strain Energy Tailoringmentioning
confidence: 99%
“…The feasible LP region is known to be convex [8,12,23], and a closed-form expression has been defined only for a limited number of combinations of the lamination parameters [41]. Expressions for a limited set of LPs have been derived by different authors.…”
Section: Related Workmentioning
confidence: 99%
“…A method for obtaining an approximate feasible region is presented in [41]. [12] developed an approach to define a feasible region for all 12 lamination parameters, which was further extended by [8]. In particular, [13] derived explicit expressions describing the feasible region for ply angles limited to {0 • , ±45 • , 90 • }.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Àh=2 cos 2h; cos 4h; sin 2h; sin 4h ð Þ z 2 dz (8) where z is the distance to the midplane, and h is the total laminate thickness [17]. The material property matrices vector C is defined as…”
Section: Transformation To Laminatementioning
confidence: 99%